Optimalisasi Aktivasi Identitas Kependudukan Digital dalam Meningkatkan Aksesibilitas Layanan Administrasi Kependudukan (Studi pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Wonogiri) - Naufal, Muhammad; Sumartono, Sumartono; Putra, Fadillah (Jurnal Ilmiah Administrasi Publik, 2025)
Digital population identity being used massively in all regions, as stated in PERMENDAGRI Number 72 of 2022, but its implementation in Wonogiri Regency has no good management so that the IKD activation, only 14.87%, because this IKD activation is intended for people who already have an ID card.  This research examines the optimisation of digital identity activation in Wonogiri Regency to see an increase in its use. This research uses Optimisation theory which has three indicators: goals, alternative decisions, and dispositions. The method used in this research is a qualitative descriptive approach in collecting primary and secondary data. The results showed that the population and Civil Registration Agency of Wonogiri Regency had optimised digital population identity well, alternative decisions were made by training village operators, picking up the ball, and collaborating with other stakeholders to build public trust in the use of IKD. In addition, data security and data management are the main focus in IKD so that the community can be well digitalised in population services.